Perinatal/maternal-fetal-infant dermatologic manifestations of SARS-CoV-2. An Overview and Implications for diagnosis, treatment, and prognosis - Young, Elaine M. (Frontiers in Pediatrics, 2022)
Early identification of the dermatologic manifestations of SARS-CoV-2 in perinatal and maternal-fetal-infant populations is essential for early intervention in the diagnosis, treatment, and prevention of short and long term sequelae. Although cutaneous signs of SARS-CoV-2 are less common in pregnant women, neonates, and infants, the recognition of related skin lesions with regard to timing, location, duration, and pattern can lead to determining disease severity. While many pediatric patients may be asymptomatic with negative SARS-CoV-2 testing, skin lesions may be the only identifiable clue of infection. SARS-CoV-2 infection in pregnancy can lead to severe life threatening illness and by understanding the cutaneous manifestations associated with SARS-CoV-2 infection, early diagnosis can be made with improved maternal-fetal outcomes. A wide array of dermatologic presentations associated with SARS-CoV-2 are reported in the literature. This review explores the expanding reports in the literature of the dermatologic presentations of skin lesions related to SARS-CoV-2 specifically in perinatal and maternal-fetal-infant health and the implications for management. The collaboration of the specialties of dermatology, pediatrics, obstetrics/gynecology, and infectious disease in the approach to SARS-CoV-2 disease can lead to a clearer understanding of the scope and presentation of this disease.